PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, LINGKUNGAN KERJA DAN DUKUNGAN INOVASI TERHADAP INOVASI ORGANISASI PERBANKAN DI KOTA MAGELANG - Suhaeli, Dahli (Jurnal Analisis Bisnis Ekonomi, 2008)
The research aim o know the influence of leadership transformasional to organizational innovation, leadership transformasional to environment work the, leadership transformasional to support innovate the, environmental influence work to organizational innovation and also support influence innovate to organizational innovation. Object this Research in Banking Magelang City, research conducted in April - Juny 2009. Sampel used by equal to 52 employees by using method of purposive sampling. Analyzer used by Partial Least Square (PLS). Result of analysis indicate that, there are influence which significant from leadership transformasional to environment work. There are negativity influence which significant from leadership transformasional to support innovate. There are influence which significant from environment work to organizational strategy innovation. There are influence which significant from support innovate to innovation innovate.